The Influence of Product Quality and Price on Purchasing Decision for Brown Sugar Boba Fresh Milk - Dino Gustaf Leonandri; Zulkifli Harahap; Rina Fitriana (Institute of Computer Science (IOCS), 2021)
Seeing the trend of Brown Sugar Boba Fresh Milk drinks among college students in Jakarta, especially nowadays, there are more and more sellers trying to fulfill this demand. Of many choices available to college students, there are factors that will come up in choosing which brand to buy. Thus, the author chooses this topic to determine whether quality and price impact on college students’ decision when buying Brown Sugar Boba Fresh Milk. The results of this study can also be used by sellers of Brown Sugar Boba Fresh Milk to find whether the quality and price expected by student consumers. This study uses quantitative research methods by collecting data using a questionnaire distributed to 150 college students in Jakarta. The results of this study indicate that 43% of product quality and product prices affect student purchasing decisions of Brown Sugar Boba Fresh Milk. Meanwhile, the most influencing indicator in product quality is the aesthetics of the product itself. And the indicator that most influences the product price is the right price and in accordance with the product obtained will attract consumers to buy.